Can CBCT change the level of confidence of oral maxillofacial surgeons in mandibular third molar management? - Ana Márcia Viana WANZELER; Heraldo Luis Dias da SILVEIRA; Rodrigo Pagliarini BULIGON; Adriana CORSETTI; Henrique Timm VIEIRA; Nádia Assein ARÚS; Mariana Boessio VIZZOTTO (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract This study analyzed the impact of CBCT on the level of confidence in diagnostic and treatment thinking in mandibular lower molar (M3M) clinical management. Thirty cases for which panoramic radiographs and CBTC images were available were selected and classified according to radiologic signs indicating the proximity of the M3M to the mandibular canal (interruption of the radiopaque borders of the canal of the mandibular canal wall, darkening of the roots, and diversion or narrowing of the canal, n = 10 for each classification). Twelve oral and maxillofacial surgeons (OMS) contributed to this study by answering two questionnaires. The first questionnaire contained a clinical description of the case and a panoramic radiograph. After 30 days, a second questionnaire with the same clinical illustrations and tomographic multiplanar reconstruction images was administered. Both questionnaires asked specialists to rate diagnostic confidence, the surgical complexity, chosen treatment, and surgical confidence. In approximately 40% of answers, CBCT images had a positive impact on ratings of diagnostic confidence and treatment thinking confidence, and in 24.4%, they increased the surgical complexity score. There was no change in the treatment plan following the use of CBCT, but the CBCT examination was a determining factor for diagnosis and treatment planning in 72.8% of the answers CBCT improved the confidence level in diagnostic and treatment thinking of the M3M management while also increasing the perceived level of surgical complexity. The findings of this study support the need to consider using CBCT in diagnosis and treatment planning for M3Ms with radiographic signs such as darkening of the roots, interruption of the radiopaque borders of the mandibular canal, or deviation of the mandibular canal and narrowing of the roots.